OLIGOMERIC CHROMIUM(III) POLICATION SPECIES-PILLARED LAYERED TETRATITANATES ANION - Hari Sutrisno; Endang Dwi Siswani (Universitas Gadjah Mada, 2007)
Intercalation of oligomeric chromium(III) polycation species in layered tetratitanates was prepared by three steps: 1) ion-exchange of H+ for K+ in potasium tetratitanates, 2) intercalation of n-alchylamine (n-propylamine, n-butylamine, n-amylamine, and n-hexylamine) compounds in layered hydrogen tetratitanates by adding an aqueous solution of 5M n-alchylamine to hydogen titanates with stiring at room temperature, and 3) intercalation of oligomeric chromium(III) polycation species by mixing butylamine-intercalated tetratitanates with an aqueous solution of CrCl3.6H2O at pH various. The procedure was carried out by Chimie Douce method. The results showed that all of n-alchylamine-intercalated tetratitanates crystallize on monoclinic crystal system with the Bravais lattice C. The hight intensity of the first peaks (200) indicated that butylamine and amylamine-intercalated tetratitanates have a remarkably high crystallinity without impurities phase. The interlayered distance (d) and the lattice parameter projected along a increase with increasing the amount of C-atoms in n-alchylamine. At pH=1.3, [CrCl(H2O)5]2+ or [CrCl2(H2O)4]+ species was pillared more efective in layered tetratitanates than [Cr(H2O)6]3+ spesies and just one spesies, Cr(H2O)6]3+ at pH=1.7. On the contrary, [Cr(OH)(H2O)5]2+ or [Cr(OH)2(H2O)4]+ was intercalated more effevtive than [Cr(H2O)6]3+ species at pH=5.3.